(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
The present study was conducted to investigate the mortality rate of lambs and associated risk factors in different production systems in Gadarif State. A total of 15,009 lambs from 300 herds were observed using Multi –Stage sampling methods. About 300 respondents were selected based on willingness and support of the owners for questionnaire survey. The results revealed that the mortality rate of the lambs were 31.5% (n = 1578), 33.4% (n = 1936) and 34.4% (n = 1453) in Central and West Gadarif, South Gadarif and East Gadarif , respectively. The difference was statistically not significant (χ2= 3.11, p-value= 0.53). The overall or crude mortality rate was 33% (n = 4967). While, the others mortality measures were as follow: the mortality rate of diarrhea was 53.3% (n = 2673) with case fatality of 18%. (n = 2673). Pneumonia gave 45% (n= 2389) for mortality rate with case fatality of 15% (n = 2389). The age specific death rate was 43.2% (n= 3992), 31.6% (n= 1213), 15.2% (n= 190) and 10% (n= 65) for age groups 0 - 2 months,2 – 4 months, 4 - 6 months and > 6 months, respectively. On the other hand, the risk factors associated with education level of the owners reveled that illiteracy was very high 50 % (n= 150), In contrast, the graduated owners were very low 1.30% (n=4), statistically, the difference was not significant (χ2=0.88, p-value= 0.99). A percentage of 67.30% (n=202) followed by 24.7% (n=74) were recorded for experience of the owners for (0 – 20 years) and (20 -40 years) respectively and no significant difference was observed (χ2=6.72p-value =0.34). Moreover, the breed was statistically significant (χ2=11.3,p-value=0.02), the mortality rate was high in Shagour breed 46.7% (n=7005), followed by Garage 31.7% (n=4757) , and Watish12 % (n=1801) .High significant level was also observed for lamb birth weight (χ2=22.7, p-value=0.001), the mortality rate was high in emaciated lambs 46 % (n=6904) but was low in over weight and average birth weight given a percentage of 0.30% (n=45) and 20.3% (n=114) respectively .Risk factors associated with management and husbandry revealed that mortality rate was high in rainy season 73.30% (n=11001) and less in winter 16.30 %( n=2446) and summer 10 .30% (n=1545), and difference was highly significant (χ2=11.7, p-value=0.001). Furthermore, the mortality was very high in pastoral production system 63% (n=9455) rather than in semi-intensive production system 24.7% (n=3707) and intensive production system 12.3% (n=1846), A high significant difference was also recorded (χ2=10.26,p-value=0.03). More owners stated presence of veterinary services 87.7% (n=253) and only 12.3% (n=37) of the owners stated a limited access to veterinary services, and no significant level was observed (χ2=0.53, p-value=0.7). In conclusion the mortality rates of lambs was found very high with diarrhea and pneumonia were the main causes of it. Hence, effort should be made to increase lambing supervision, improve management of newborn lambs, and prevent diarrhea and respiratory diseases